Morphology related photodegradation of low-band-gap polymer blends - Wang, Xiao; Egelhaaf, Hans-Joachim; Mack, Hans-Georg; Azimi, Seyed Hamed; Brabec, Christoph; Meixner, Alfred J.; Zhang, Dai (Advanced Energy Materials, 2014)
The morphology related photodegradation of low band-gap polymer blends is investigated using optical microscopy and scanning probe microscopy. Poly[2,6-(4,4-bis-(2-ethylhexyl)-4H-cyclopenta[2,1-b;3,4-b′]dithiophene)-alt-4,7(2,1,3-benzothiadiazole)] (C-PCPDTBT):[6,6]-phenyl C61-butyric acid methyl ester (PCBM) blend films without and with ODT, as well as poly[(4,40-bis(2-ethylhexyl)dithieno[3,2-b:20,30-d]silole)-2,6-diylalt-(2,1,3-benzothiadiazole)-4,7-diyl] (Si-PCPDTBT):PCBM blend films exposed to a focused 632.8 nm laser under ambient condition with and without inert gas protection are studied. The photodegradation of the polymer starts in the vicinity of the PCBM molecules (first sphere degradation), which effectively blocks the electron transfer processes. Stern-Volmer type kinetics are observed in the C-PCPDTBT:PCBM blend with ODT, which indicates that only a small number of photo-oxidized monomer units act as quenchers of the C-PCPDTBT polymer luminescence. Furthermore, in addition to the permanent damage of the polymer molecules, as witnessed from their Raman intensity decrease, the polymer photoluminescence demonstrates partial reversible recovery when inert gas protection is resumed, indicating the involvement of temporary polymer/O-charge transfer complexes in the photodegradation process.
Keywords: Nanoscale morphology; Phase separation; Photodegradation; Polymer blend films